Mutual information in natural position order of electroencephalogram is significantly increased at seizure onset. - Hall CW Jr; Sarkar A; Hall, Charles W Jr; Sarkar, Atom (Medical & Biological Engineering & Computing, 2011)
Epilepsy affects an estimated 60 million people worldwide. As many as 50% of people with epilepsy will continue to have seizures despite therapeutic dosages of appropriately selected antiepileptic drugs. Among proposed treatment modalities for persons with medication refractory epilepsy are implantable devices that rapidly detect and abort seizures. Computational resources in these devices are limited and much effort is directed to improving the efficiency of seizure detection. The goal of this study is to determine if electroencephalogram (EEG) may be reduced by the method of natural position order in a way that increases computation speed and reduces system memory requirements while preserving features relevant to detecting seizure onset. In this study we show increased mutual information (MI) at seizure onset in simultaneous channels of EEG reduced by natural position order with a 40-fold reduction in computation time and a fivefold reduction in system memory requirements. The trade-offs to EEG reduction by natural position order include decreased bandwidth and increased noise sensitivity.